2017
DOI: 10.1083/jcb.201606047
|View full text |Cite
|
Sign up to set email alerts
|

RASSF4 controls SOCE and ER–PM junctions through regulation of PI(4,5)P2

Abstract: RAS association domain family 4 (RASSF4) is involved in tumorigenesis. Chen et al. show that RASSF4 regulates store-operated Ca2+ entry and ER–PM junctions by affecting PI(4,5)P2 levels. RASSF4 interacts with and regulates the activity of ARF6, an upstream regulator of PIP5K and PI(4,5)P2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
74
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 75 publications
(122 reference statements)
10
74
2
Order By: Relevance
“…Turning off ORPs this way will affect PS transport and perhaps that of other lipids that may impact the STIM1/Orai1 function. Another recent study identified RASFF4, one of the Ras association domain family proteins, as regulators of SOCE via controlling PI(4,5)P 2 production thus maintaining ESyt2 and ESyt3 PM contacts (Chen et al 2017). Higher cytoplasmic Ca 2+ increases that are evoked by Ca 2+ ionophores, or during PM damage and repair can activate PLC without receptor stimulation, but also initiate more profound changes in the distribution of other lipids, such as DAG (see above) and PS.…”
Section: Ca 2+ Has Important Roles In the Control Of Er-pm Contactsmentioning
confidence: 99%
“…Turning off ORPs this way will affect PS transport and perhaps that of other lipids that may impact the STIM1/Orai1 function. Another recent study identified RASFF4, one of the Ras association domain family proteins, as regulators of SOCE via controlling PI(4,5)P 2 production thus maintaining ESyt2 and ESyt3 PM contacts (Chen et al 2017). Higher cytoplasmic Ca 2+ increases that are evoked by Ca 2+ ionophores, or during PM damage and repair can activate PLC without receptor stimulation, but also initiate more profound changes in the distribution of other lipids, such as DAG (see above) and PS.…”
Section: Ca 2+ Has Important Roles In the Control Of Er-pm Contactsmentioning
confidence: 99%
“…Interestingly, in those models, the rate of the PI 4-kinase and PI 5-kinases had to be elevated temporarily during G q -coupled receptor activation to account for the sustained production of IP 3 (Dickson et al, 2013). Supporting these data, Chen et al (2017) find that recovery of PI(4,5)P 2 after G q receptor activation is faster with RAS SF4 overexpression. Further experiments are certainly required to determine whether this hypothesis is correct, but given its upstream location and effects on Arf6 activity, RAS SF4 is ideally positioned to be a key regulator of such a pathway.Many of the RAS SF proteins have been shown to play a role in tumor suppression (van der Weyden and Adams, 2007).…”
mentioning
confidence: 67%
“…Thus, expressional changes in RAS SF4 correlate with PM PI(4,5)P 2 abundance to control SOCE and ER-PM junctions. Chen et al (2017) also provide insight into the mechanism through which RAS SF4 may regulate the activation of Arf6 to control PM PI(4,5)P 2 . Using several ARF6 mutants, which mimic different nucleotide-binding states, they find that RAS SF4 preferentially binds the inactive, GDP-bound form of Arf6 (Arf6-GDP).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…During this period, the rapid recruitment of Nir2 to ER‐PM contacts may also facilitate rapid PtdIns(4,5)P 2 re‐synthesis, which would help to reinforce the binding of E‐Syt1 to the PM . A related model has since implicated an additional Ca 2+ ‐sensitive regulator of ER‐PM contacts, Ras association domain family 4 (RASSF4), which directly activates an upstream regulator of PIP5Ks, the small G‐protein adenosine diphosphate ribosylation factor 6 (ARF6), which stimulates the local production of PtdIns(4,5)P 2 from PtdIns4P to perhaps sustain the PM‐binding of E‐Syt2 and E‐Syt3 . Taken together, these collected works strongly suggest that the E‐Syts serve an important function related to the lipid homeostasis of the PM and are also important molecular tethers that stabilize ER‐PM contacts for diverse functions related to signal transduction and ion transport.…”
Section: Additional Lipid Transfer Proteins With Functions At Er‐pm Cmentioning
confidence: 99%